Association between objectively measured body composition, sleep parameters and physical activity in preschool children: a cross-sectional study. Issue 1 (20th January 2021) - Wyszyńska, Justyna; Matłosz, Piotr; Asif, Muhammad; Szybisty, Agnieszka; Lenik, Paweł; Dereń, Katarzyna; Mazur, Artur; Herbert, Jarosław
Abstract : Objective: Associations between self-reported sleep duration and obesity indices in children are well recognised; however, there are no studies on associations between objectively measured other sleep parameters and physical activity with body composition in preschoolers. Therefore, the aim of this study was to determine the associations between sleep parameters and moderate-to-vigorous physical activity (MVPA) with body composition indices in preschoolers using objective measures. Design: A cross-sectional study. Participants: The study group consisted of 676 children aged 5–6 years, who were enrolled in kindergartens in the 2017/2018 school year. Outcome measures: Sleep parameters and MVPA were measured using accelerometers for 7 days. Bioelectrical impedance analysis was used to estimate body composition. Results: Sleep duration and sleep efficiency were inversely associated with body fat percentage (BFP) (β=−0.013 and β from –0.311 to −0.359, respectively) and body mass index (BMI) (β from −0.005 to −0.006 and from −0.105 to –0.121, respectively), and directly associated with fat-free mass (FFM) (β from 0.010 to 0.011 and from 0.245 to 0.271, respectively) and muscle mass (β from 0.012 to 0.012 and from 0.277 to 0.307, respectively) in unadjusted and adjusted models. BFP was inversely associated with MVPA and positively associated with number of awakenings and sleep periods. Number of sleep periods was inversely associated with FFM, and positively with BMI and muscle mass. Correlation matrix indicated significant correlation between BFP, FFM and muscle mass with sleep duration, sleep efficiency, number of sleep periods and MVPA. Conclusions: Periodic assessment of sleep parameters and MVPA in relation to body composition in preschool children may be considered, especially in those who are at risk for obesity.